O perfil do desenvolvimento socioeconômico dos municípios paranaenses que possuem agroindústria canavieira: estudo de caso - Deliberali, Edson Antonio (2010)
This study has the objective of expose the profile of socioeconomic development of municipalities of Paraná that have sugar-cane Agro-Industry (in this figure as the main force). First of all was used the analysis method of principal components to create socioeconomic development Indicator (IDSE) to Paraná cities. After that is elected a city with a low (IDSE) and another with a high one to be done a individual case study. In case of low IDSE the search showed a lack of joint actions between the community and the local unit producing to improve population life. The only relationship directly in this case evidenced by generation jobs provided by the plant versus income (salary) paid to its collaborators. The plant uses to hire workers with permanent housing in the city or region. The mechanization of cane cutting and adult sand young people illiteracy is a short-term concern for the local population. In case of high IDSE the relation between local agro-industry and the city is more intense. The unit participates with social activities, and promotes indoors activities at the company to improve some indicators. The city has bigger opportunities of job vacancies, but also tends in a near future encounter with implementation of the mechanization of its sugar cane plantation. The hand-manpower available for the plant consists of three profiles worker, the former worker and resident in municipality most often occupies other positions that do not cutting sugar cane, and frequent training courses during the off-season, the second worker the region, and the third wheel is the worker, other regions of the country coming to town and settles provisionally (during harvest) the end of the harvest they return to their homeland bringing with economies who managed to save. That way that way for this two cases in particular, that the sugar industry influence the local economy of the town which is located, because it directly promotes employment and income, which provides access to consumer goods, health, education and others, and indirectly through actions Community influences the improvement of Socioeconomic municipalities indicators where they are located.